Kompetensi Guru Pendidikan Agama Kristen di Era Society 5,0 - Wassar, Sarah; Indriati Tjipto Purnomo; Ipan Morris Pangaribuan; Simon Simare Mare; Stefanus Alpha Yani Kristiono (Sekolah Tinggi Teologia Kerusso Indonesia, 2024)
Educators or teachers who are in the era of society 5.0 must take advantage of these three things, namely: Internet of things in the world of education (IoT), Virtual/Augmented reality in the world of education, and the use of Artificial Intelligence (AI) to find out and identify the learning needs needed by students.